Gerakan Salafi dan Deradikalisasi Islam di Indonesia - Slamet Muliono; Andi Suwarko; Zaky Ismail Ismail (Religió: Jurnal Studi Agama-agama, 2019)
The Salafi (Wahabi) movement in Indonesia in recent decades is growing rapidly. Generally, the group is often considered as part of takf?riy, radical or terrorist group considering its similarity in rejecting the heresy (bidah) practices and its view on democracy. This research attempts to explore how its religious teaching and strategies as well as its compatibility to deradicalization efforts. The research uses Hertbert Blumer's theory which classifies the development of a movement in four stages; social chaos, popular excitement, formalization and institutionalization. This research found that their Islamic teaching merely refers to the model of Islam practiced by three early generations. Meanwhile, the strategy undertaken is focused on teaching tauhid through education that has been purified (ta?fiyah) and tarbiyah. Compatibility to deradicalization of this group lies on the evidence that Salafi is different with takf?riy, radical or terrorist group. Moreover, they believe that Pancasila is not against Islam.